2020
DOI: 10.1007/s12630-020-01668-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of gastric content in fasted patients before elective laparoscopic cholecystectomy: a prospective observational single-cohort study

Abstract: Background Patients with symptomatic gallbladder diseases exhibit delayed gastric emptying. We evaluated the residual gastric content in fasted patients scheduled for elective laparoscopic cholecystectomy because of symptomatic gallbladder disease using ultrasonography. Methods This prospective observational single-cohort study was approved by the Institutional Review Board, and written informed consent was obtained from all included patients. Before anesthesia induction, the gastric antrum was examined by ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…One notable aspect of this study was that residual GV > 1.5 ml/kg was observed in six patients before the second TKA operation that fortunately did not manifest as pulmonary aspiration. Although the strict threshold of GV that increases the risk of pulmonary aspiration is controversial, recent reports have announced that patients with GV > 1.5 ml/kg are a high-risk group for pulmonary aspiration [ 13 , 14 ], and residual GV > 1.5 ml/kg was occasionally observed in fasted patients suggesting incomplete gastric emptying [ 5 , 17 ]. However, there was a report that no one had a residual GV > 1.5 ml/kg after 2 h of drinking carbohydrate-containing fluid in ambulatory surgery [ 18 ], and in our study, there was no patient with a residual GV > 1.5 ml/kg in the first TKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One notable aspect of this study was that residual GV > 1.5 ml/kg was observed in six patients before the second TKA operation that fortunately did not manifest as pulmonary aspiration. Although the strict threshold of GV that increases the risk of pulmonary aspiration is controversial, recent reports have announced that patients with GV > 1.5 ml/kg are a high-risk group for pulmonary aspiration [ 13 , 14 ], and residual GV > 1.5 ml/kg was occasionally observed in fasted patients suggesting incomplete gastric emptying [ 5 , 17 ]. However, there was a report that no one had a residual GV > 1.5 ml/kg after 2 h of drinking carbohydrate-containing fluid in ambulatory surgery [ 18 ], and in our study, there was no patient with a residual GV > 1.5 ml/kg in the first TKA.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that fasting time was not associated with residual gastric volume (GV), showing that the incidence of full stomach was 35% in patients who had unplanned surgery and fasted for at least 6 h [ 4 ]. Even in scheduled laparoscopic cholecystectomy, 13% of patients showed a full stomach despite adherence to the recommended fasting time [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with Perlas grade I had < 100 mL gastric content, whereas those with grade II had obvious gastric content in both supine and RLD positions[ 23 ]. Moreover, GV/W > 1.5 mL/kg helps determine the risk of reflux and aspiration[ 24 - 26 ]. In our study, the number of patients with Perlas grade II and GV/W > 1.5 mL/kg did not differ among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, 2.7-6.2% of fasting patients were defined as a sonographic full stomach state before elective surgery [17,18]. Furthermore, despite following the fasting guidelines, 13% of the patients planned for elective laparoscopic cholecystectomy for symptomatic gallbladder disease appeared as a full stomach, determined by ultrasound imaging, before the anesthesia induction [19]. Continuous positive airway pressure using a facemask can result in gastric insufflation.…”
Section: Discussionmentioning
confidence: 99%